Youtube “Satu Persen” Sebagai Sarana Komunikasi Massa Pengembangan Diri Mahasiswa - Ervita Riliana; Nina Yuliana (Lembaga Pengembangan Kinerja Dosen, 2023)
YouTube, which is a means of mass communication, now has an impact on student self-development. YouTube